Application of The Wakalah Bil Ujrah Wa Tabarru Agreement at Pt. Takaful Public Branch Padang Insurance - Indra, Novalia; Johanna, Anne; Avinash, Buschhaus (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2021)
The main problem in this thesis is